The ascent of Bitcoin: Bibliometric analysis of Bitcoin research - Ahmet Faruk Aysan; Hüseyin Bedir Demirtaş; Mustafa Saraç (Journal of Risk and Financial Management, 2021)
Bitcoin, as the first decentralized cryptocurrency, pioneers the cryptocurrency markets, both in terms of market capitalization and scientific interest. In this paper, we performed a comprehensive bibliometric study of the Bitcoin-related literature. Using the Scopus database, we created a sample that comprises 4495 documents written in the 2011-2020 period. Furthermore, we provided insights about dimensions such as the change in the number of publications over the course of years, the main research areas, types of published documents, most important platforms and sources of Bitcoin publications, highly cited studies, productive authors, author's countries, and finally main funders of Bitcoin-related research. Lastly, our bibliometric study manifests the current state and future path of Bitcoin literature from distinct perspectives.
Keywords: G19; E4; 330; Bitcoin; blockchain; bibliometrics; cryptocurrencies; research; Scopus; VOSviewer